(untitled) (Journal of the College of Basic Education, 2022)
Gifted people represent an important human resource that outweighs the value of other material resources if they are given opportunities to develop their talents and abilities and develop them and put them in the service of their societies (Gaddafi, 1996: 20). Behavior, and behavior is the outcome of many subjective (personal) and objective (environmental) factors. Therefore, this behavior of gifted people must be affected by some factors or linked to them, such as anxiety, as anxiety occupies a prominent place in psychology, as it is considered one of the basic factors for mental health.